Balance deficiencies in women with fibromyalgia assessed using computerised dynamic posturography: a cross-sectional study in Spain. Issue 7 (1st August 2017) - Pérez-de-Heredia-Torres, Marta; Huertas-Hoyas, Elisabet; Martínez-Piédrola, Rosa; Palacios-Ceña, Domingo; Alegre-Ayala, Jorge; Santamaría-Vázquez, Montserrat; Fernández-de-las-Peñas, César
Abstract : Objectives: Our aims were (1) to compare the sensory organisation of balance control and balance strategies between women with fibromyalgia (FM) and healthy women; (2) to investigate which sensory component, that is, vestibular, visual or somato-sensory, is the most affected in FM and (3) to determine the associations between the functional independence measure (FIM) and balance responses in FM. Design: Cross-sectional observational study. Setting: Urban regional hospital and university (Universidad Rey Juan Carlos, Madrid, Spain). Participants: Twenty women with FM and 20 matched healthy women. Primary/secondary outcome measures: The sensory organisation test (SOT) was used to determine postural sway and balance during six different conditions with subjects in a standing position. The FIM was used to determine the level of functional independence in daily life activities (ADL). Between-group differences were analysed with analysis of covariance, and the Spearman's test was used for correlations. Results: Significant differences between-groups and between-conditions were found for all SOT conditions (all, p<0.001): women with FM showed lower scores being the vestibular score the most affected. Different correlations between SOT conditions and some specific ADL were observed in the FM group: bathing activity and balance condition 6 (rs =0.541; p<0.001), bed transfers activity and conditions 2 (rs =0.491; p<0.001) and 3 (rs =0.510; p<0.001), positioning strategy six and dressing the upper (rs =0.530; p<0.001) or lower (rs =0.562; p<0.001) body, and toileting (rs =0.521; p<0.001): the greater the loss of balance, the greater the interference on some daily life activities. Conclusions: Women with FM exhibited balance deficiencies and used different strategies for maintaining their balance in standing, which was associated with a negative impact on functional independence.